Inter-comparison of two air quality modelling systems for a case study in Berlin. (11th May 2004) - Suppan, Peter; Skouloudis, Andreas N.
A case study was carried out to compare two air-quality models (UAM-V and MCCM) in the region of Berlin. These are two well documented regional and urban models which were run independently with their own meteorological drivers and emission inventories with the aim to describe a specific ozone episode. Numerous applications in the US and in Europe have shown the good performance of these models. The comparison focuses on basic differences of the chemical part of the models. Differences in simulated concentrations for O3, NO2 and CO are shown to be due to different handling of model features (e.g. nesting) and emission inventories.